FARMER'S KNOWLEDGE AND ECONOMIC ANALYSIS OF USING OF Chloris gayana GRASS AS BUFFALO FEED IN PASTORAL LAND - Supardi Rusdiana; Iwan Herdiawan (Buletin Peternakan, 2017)
The research objective was to obtain information about the knowledge of farmers towards Chloris gayana grass and economic feasibility of buffalo farming and farmer level as a first step for further activities. The study was conducted in the village Mekarsari Cibadak Subdistrict Lebak District of Banten Province, with a survey method in 2016, using questionaire  and interviews to 20 farmers. Primary data were obtained from the farmer and secondary data obtained from the local Office. The collected data were tabulated and analyzed descriptively, quantitatively and economically. In male buffalo rearing, farmer’s profit was able to reach Rp3.170.000,-/head, with B/C ratio was 1.06. While buffalo cow-calf operation gave profit as Rp4.630.000,-/head, with B/C ratio was 1.06. It seems that keeping buffalo to produce meat was more porfitable compared to cow-calf operation. It resulted the development of bufallo in Kampung Curug Mekar Sari village Cibadak District of Lebak, Banten was slow. Planting Chloris gayana grass can support farmer and increase the economic scale of buffalo farmers.